Development of an oral mucosa equivalent using a porcine dermal matrix. Issue 3 (April 2017) - Basso, F.G.; Hebling, J.; Marcelo, C.L.; de Souza Costa, C.A.; Feinberg, S.E.
Abstract: We evaluated the suitability of a porcine acellular dermal matrix for the development of a 3-dimensional oral mucosal equivalent using an ex vivo-produced oral mucosal equivalent (EVPOME). Oral keratinocytes were seeded in a submerged model, and then in an air-liquid interphase model, using Transwell ® inserts. EVPOME showed good cell viability and increased glucose consumption over time. Histological evaluation showed that stratified differentiated epithelium had formed in all matrices.